Meta-analysis of Complementary and Alternative Intervention on Menstrual Distress - Jung Hyo Kim; Mi Kyung Park; Mi Ra Oh (Korean Society of Women Health Nursing, 2013)
PURPOSE: This study was to analyze the effect size of complementary and alternative intervention studies in reference to dysmenorrhea and menstrual distress. METHODS: In order to conduct a meta-analysis, a total of 393 studies were retrieved from the database. Twenty-eight studies that were published from March 2001 to February 2011 were selected. RESULTS: Intervention studies included seven studies on aromatherapy, five on auriculotherapy, three on each Koryo-Sooji-Chim and moxibustion, two on each heat therapy and magnetic therapy and six on other therapy. The effect size of the intervention studies on dysmenorrhea and menstrual distress was greater than 0.48 for Koryo-Sooji-Chim, moxibustion, aromatherapy, auriculotherapy and other therapy. CONCLUSION: This study suggests that drug free therapy can reduce the levels of menstrual distress, despite the small number of intervention studies and randomized controlled trials.